Genomic stability prevails in North-African hepatocellular carcinomas - (:unkn) unknown (My University, 2007)
The molecular pathogenesis of hepatocellular carcinoma, a tumour characterized by a vast clinical heterogeneity, remains unexplored outside Europe and Eastern Asia. We analysed by direct sequencing or loss of heterozygosity assay, the common targets of genomic alterations in 42 hepatocellular carcinomas collected in western North-Africa. Overall, genomic instability was uncommon, allelic losses affecting mostly chromosomes l p, 4q, 8p and 17p (24-28% of cases). CTNNBI and TP53 were infrequently mutated (9 and 17% of cases, respectively). Surprisingly. TP53 mutation R249S, diagnostic of aflatoxin B1 exposure, usually frequent in Africa, was exceptional (one case), indicating that in western North-Africa, hepatocellular carcinoma genetics differs markedly from that of the remainder of the continent. (C) 2007 Editrice Gastroenterologica Italiana S.r.l. Published by Elsevier Ltd. All rights reserved.
Keywords: African Research